Seasonal relative abundance of fish larvae in Helleh River estuary (north of the Persian Gulf, Iran) (Biodiversitas Journal of Biological Diversity, 2017)
Paighambari SY, Pouladi M, Parsa M, Mehdipour N, Haghighatjou N, Jabaleh A, Hedayati A. 2017. Seasonal relative abundance of fish larvae in Helleh River estuary (north of the Persian Gulf, Iran). Biodiversitas 18: 541-547. Study of abundance and composition of fish larvae in order to examine their association with salinity, temperature, dissolved oxygen and transparency was conducted in Helleh River estuary in the north of the Persian Gulf. Samples were collected using Bongo net with 500 Î¼m mesh size and 60 cm mouth diameter size in five selected stations from August 2011 to May 2012. Generally, 1637 fish larvae were isolated from 19 families that most of them were belong to Clupeidae. Seasonal relative abundance (SRA) of fish larvae varied and Clupeidae (39.90%) and Gobiidae (14.35%) in summer; Clupeidae (26.23%) and Sparidae (21.82%) in autumn; Clupeidae (34.43%) and Hemiramphidae (12.02%) in winter; Clupeidae (47.93%) and Sparidae (13.67%) in spring were most abundant than others. Overall, families namely Clupeidae (39.28%), Gobiidae (12.58%) and Sparidae (10.57%) had the highest and Carangidae (0.92%) had the lowest relative abundance during the sampling period. ANOVA test also showed a significant difference between summer and autumn with spring and winter (P
Keywords: Fish larvae; Helleh River; estuary; Persian Gulf; Iran